KEPEMIMPINAN KEPEMIMPINAN TRANSFORMASIONAL ISLAMI: MENGUATKAN DASAR-DASAR PENDIDIKAN ISLAM DALAM MANAJEMEN SEKOLAH DI RA MA’ARIF NU 002 SAMARINDA - Al Khafidah Arifah Ya Nur Rohmah; Ahmad Ridani; Bahrani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of Islamic transformational leadership in strengthening the foundational values of Islamic education at RA Ma’arif NU 002 Samarinda. Islamic early childhood institutions face challenges such as modernization, quality demands, and rapid social change; thus, they require leadership that is not only managerially effective but also spiritually grounded. This research adopts a qualitative case study approach using interviews, observations, and documentation. The findings reveal that the principal practices Islamic transformational leadership through moral exemplification, inspirational motivation, teacher empowerment, and the development of a religious school culture. The principal successfully integrates Islamic values such as trustworthiness, morality, and worship into managerial activities and classroom practices. School culture transformation is evident in the increased collaboration among teachers, improved professionalism, and enhanced religious behavior of students. Despite challenges including limited facilities, varying teacher competencies, and diverse parental understanding, transformational leadership proves effective in strengthening the Islamic identity of the institution. This study highlights the importance of visionary and transformative Islamic leadership in preserving the core values of Islamic education at the early childhood level amid global pressures.